A Hybrid-Monolayer Fluorescence Probe Towards the Detection of Ultratrace Co2+ Ion at Surface of SiO2 Nanoparticles - Zhu, Dechun; Chen, Hong; Sun, Hong; Si, Jingyu; Shi, Jianjun; Gao, Daming (Asian Journal of Chemistry, 2013)
This paper reports a resonance energy transfer-amplifying fluorescence quenching at the surface of silica nanoparticles for the ultrasensitive and ultratrace detection of Co2+ ion in solution. The nanoparticle-assembled arrays on silicon wafer can sensitively detect down to ca. 1 nM Co2+ with the use of only 10 μL of solution (ca. 60 pg Co2+).